2012
DOI: 10.1111/j.1601-183x.2012.00837.x
|View full text |Cite
|
Sign up to set email alerts
|

FKBP5 and emotional neglect interact to predict individual differences in amygdala reactivity

Abstract: Individual variation in physiological responsiveness to stress mediates risk for mental illness and is influenced by both experiential and genetic factors. Common polymorphisms in the human gene for FK506 binding protein 5 (FKBP5), which is involved in transcriptional regulation of the hypothalamic-pituitary-adrenal (HPA) axis, have been shown to interact with childhood abuse and trauma to predict stress-related psychopathology. In the current study, we examined if such gene-environment interaction effects may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
128
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 168 publications
(145 citation statements)
references
References 74 publications
15
128
0
Order By: Relevance
“…The present study is in accordance with a recent finding demonstrating a G 9 E interaction of FKBP5 with EN on amygdala activity (White et al 2012). In both our study and that of White et al (2012), homozygotes for the rs1360780 T allele showed increasing activity in the right amygdala with the level of childhood neglect, while C homozygotes exhibited decreasing activity, with heterozygotes being intermediate.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…The present study is in accordance with a recent finding demonstrating a G 9 E interaction of FKBP5 with EN on amygdala activity (White et al 2012). In both our study and that of White et al (2012), homozygotes for the rs1360780 T allele showed increasing activity in the right amygdala with the level of childhood neglect, while C homozygotes exhibited decreasing activity, with heterozygotes being intermediate.…”
Section: Discussionsupporting
confidence: 82%
“…In both our study and that of White et al (2012), homozygotes for the rs1360780 T allele showed increasing activity in the right amygdala with the level of childhood neglect, while C homozygotes exhibited decreasing activity, with heterozygotes being intermediate. However, in contrast to White et al (2012), who found a significant increase in T homozygotes, a significant decrease in C homozygotes was obtained in our study. Several reasons may be responsible for this discrepancy, such as differences in sample composition, reported level of EN, and implementation of the imaging paradigm employed.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations